2010
DOI: 10.1021/ml100046d
|View full text |Cite
|
Sign up to set email alerts
|

Carbamylation of N-Terminal Proline

Abstract: Protein carbamylation is of great concern both in vivo and in vitro. Here, we report the first structural characterization of a protein carbamylated at the N-terminal proline. The unexpected carbamylation of the R-amino group of the least reactive codified amino acid has been detected in high-resolution electron density maps of a new crystal form of the HIV-1 protease/saquinavir complex. The carbamyl group is found coplanar to the proline ring with a trans conformation. The reaction of N-terminal with cyanate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…While slightly acidic medium (pH 6.3–6.5) have been reported as optimum for protease production by Bacillus sp. MIG [43] and B. cereus SIU1 [119], slightly alkaline medium (pH 8.0–8.5) has been reported to be optimum for protease production by B. licheniformis IKBC-17[89], B. subtilis IKBS 10 [89], Bacillus macerans IKBM-11 [89], Bacillus amovivorus [111] and Aspergillus niger [30]. The reason behind this kind of observation is not yet very clear.…”
Section: Alkaline Protease Production Under Submerged Fermentationmentioning
confidence: 99%
“…While slightly acidic medium (pH 6.3–6.5) have been reported as optimum for protease production by Bacillus sp. MIG [43] and B. cereus SIU1 [119], slightly alkaline medium (pH 8.0–8.5) has been reported to be optimum for protease production by B. licheniformis IKBC-17[89], B. subtilis IKBS 10 [89], Bacillus macerans IKBM-11 [89], Bacillus amovivorus [111] and Aspergillus niger [30]. The reason behind this kind of observation is not yet very clear.…”
Section: Alkaline Protease Production Under Submerged Fermentationmentioning
confidence: 99%
“…The expressed PR was purified from inclusion bodies by a modified method of Louis and co-workers [45]. Using consolidated refolding and crystallization protocols [23], the protein (1–2 mg·mL −1 ) was preincubated with a 5-fold molar excess of the inhibitor, EPX.…”
Section: Methodsmentioning
confidence: 99%
“…It is widely acknowledged that structural information on protein targets complexed with inhibitors helps guide improved synthesis of lead compounds [20,21,22,23,24]. However, the direct use of protein crystals in making new ligands for a particular protein target by in-situ synthesis is just emerging [25].…”
Section: Introductionmentioning
confidence: 99%
“… 6 Two major sites of carbamylation reaction are, N α -amino moiety of a protein N-terminus and the N ε -amino moiety of proteins' lysine residues. 7 In vitro studies have shown that reactive oxygen species formed during carbamylation process may alter proteins' properties. 6 Carbamylation plays significant role in progression of various diseases by altering proteins' charge, structure and function.…”
Section: Introductionmentioning
confidence: 99%